Performing percutaneous nephrolithotomy under modified local anesthesia - Yu, Yue; Hu, Jieping; Liu, Wei; Peng, Zhixiong; Wang, Mengzhen; Zhou, Xiaochen; Xi, Haibo (Frontiers in Surgery, 2022)
Objective This pilot study aimed to assess the practicability and effectiveness of percutaneous nephrolithotomy (PCNL) with vacuum-assisted nephrostomy sheaths for patients under modified local anesthesia (m-LA). Methods PCNL with a vacuum-assisted nephrostomy sheath under m-LA was performed in 83 patients between November 2020 and May 2021. An 18F or 20F ClearPetra Nephrostomy Sheath connected vacuum aspiration was used in surgery to keep low pressure in the renal pelvis. For LA, lidocaine and ropivacaine hydrochloride were 1:1 mixed and instilled under ultrasound guidance through the percutaneous nephrolithotomy channel directed toward the design calix. Demographic characteristics, stone characteristics, visual analogue scale (VAS) score, vital signs, operation time, complications, and stone clear rate were recorded and analyzed. Results All operations were completed. The mean VAS score was 3.9 ± 1.0. The mean operation time was 55.1 ± 23.6 min. The changes for systolic blood pressure, diastolic blood pressure, and heart rate were 3 ± 21 mmHg, 1 ± 14 mmHg, and −6 ± 14 beats/min, respectively. The change for hemoglobin was −10.7 ± 10.9 g/L. The change for C-reactive protein was 5.39 ± 43.1 mg/L. The total stone-free rate was 69.9% (93.8% for simple stones and 54.9% for complex stones). Conclusion Performing PCNL with vacuum-assisted nephrostomy sheaths under modified local anesthesia under ultrasound guidance was found to be strongly practical and effective.